Empirical Formulas to Predict the Maximum Scour Depth With Debris Accumulation Around A Single Cylindrical Bridge Pier: An Experimental Study - Mahmoud Saleh Al-Khafaji; Aysar Al-Awadi (Engineering and Technology Journal, 2020)
The probability of debris accumulation near bridge piers during the heavy storm and river flood convert the hydraulic action of flow and increase the scour depth due to the reduction of flow area and the increase in velocity of flow. In this paper, the effects of debris accumulation length, width and submerged depth on scour depth near bridge pier were investigated. An experimental study for three groups of woody debris accumulation was conducted under clear water condition to investigate the effects on maximum scour depth. The results showed that the increase of blocked area of debris to 27% increases the scour depth by approximately 140%. Furthermore, two empirical exponential formulas was proposed to predict the effect of debris on the maximum scour depth and the modification factor required for single pier. Well agreement was obtained for both derived formulas with coefficient of determination (R2) of 0.96.